An Analysis of Opportunities, Challenges and Key Strategic Implications Connected with the Utilization of the Internet of Things by Contemporary Business Organizations - Wielki, Janusz (International Journal of Engineering and Technology, 2018)
The rapid development of the Internet of Things and its growing influence on functioning of business organizations and utilized by them business models was the main motivation of undertaking the research presented in the paper. In this context the most important areas of opportunities created with the development of this concept were determined. The main internal and external challenges of a technical and non-technical nature were also identified. The major finding of the paper is suggested in its final part a strategic framework connected with the implementation of the concept of the Internet of Thing in business organizations.Â Â